Business Critical: Understanding a Company’s Current and Desired Stages of Corporate Responsibility Maturity - Ainsbury, R.; Grayson, David (Cranfield University, 2014)
It’s been a while since the Corporate Responsibility profession took stock of its collective wisdom on where we have been, and where we are going on running businesses responsibly. Meanwhile hardly a week goes by without a helpful suggestion from the outside world on how an organisation should improve its economic value, social usefulness and environmental efficiency; and it is very easy to spot businesses that get their social, environmental and economic decisions out of balance: these organisations hit the headlines seemingly within nanoseconds. On the upside, businesses are increasingly taking an approach that builds an Environmental, Social and Governance (ESG) premium into the core economic valuation. This is achieved by those organisations which bring in a diverse set of views to inform risk and reputation management activities, and to build a research and development pipeline for the future. This is managing both the negative and the positive social, environmental and economic impacts.